2017
DOI: 10.1186/s12989-017-0215-3
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-regulated microRNA-574-5p underlies synaptic and cognitive impairment in response to atmospheric PM2.5 aspiration

Abstract: BackgroundPM2.5 (particulate matter ≤ 2.5 μm) is one of the leading environmental risk factors for the global burden of disease. Whereas increasing evidence has linked the adverse roles of PM2.5 with cardiovascular and respiratory diseases, limited but growing emerging evidence suggests that PM2.5 exposure can affect the nervous system, causing neuroinflammation, synaptic dysfunction and cognitive deterioration. However, the molecular mechanisms underlying the synaptic and cognitive deficits elicited by PM2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 93 publications
7
58
0
Order By: Relevance
“…regions (Fonken et al, 2011), reduced synaptic function (Ku et al, 2017) in CA1 neurons (Davis et al, 2013), and decreased myelin basic protein in white matter and increased atrophy of neurites in the CA1 region (Woodward et al, 2017) have been observed. These neurotoxicological data collectively suggest that some hippocampal subfields may be more sensitive than others to the adverse PM-effects.…”
Section: Sensitivity Analysesmentioning
confidence: 92%
See 1 more Smart Citation
“…regions (Fonken et al, 2011), reduced synaptic function (Ku et al, 2017) in CA1 neurons (Davis et al, 2013), and decreased myelin basic protein in white matter and increased atrophy of neurites in the CA1 region (Woodward et al, 2017) have been observed. These neurotoxicological data collectively suggest that some hippocampal subfields may be more sensitive than others to the adverse PM-effects.…”
Section: Sensitivity Analysesmentioning
confidence: 92%
“…Several animal studies have demonstrated that inhaled PM 2.5 exposures affect various neural systems thought to underlie these episodic memory processes (Fonken et al, 2011;Cheng et al, 2017;Ku et al, 2017;Liu et al, 2018). Few longitudinal epidemiological studies examined the association between PM 2.5 and episodic memory (Weuve et al, 2012;Tonne et al, 2014;Wurth et al, 2018), and the majority of these studies utilized composite scores with mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…1 PM2.5 can be suspended in the air for long periods of time and is believed to pose risks to health. [2][3][4][5][6] Allergic conjunctivitis (AC) is an eye inflammation condition caused by allergic reactions to substances such as pollen or mild spores. 7 It is one of the most common ocular surface diseases encountered in clinical practice and may come in either acute or chronic types.…”
mentioning
confidence: 99%
“…For one thing, microglia could protect neuron cells by engulfing alien substances, clearing cell fragments, Aβ deposition and etc. For another, microglia related inflammatory responses could contribute to the increasing of Aβ deposition, neuron damage and even AD risk [22,23].…”
Section: Introductionmentioning
confidence: 99%